The Influence Of Service Quality On Member Satisfaction At Kspps Bmt Insan Madani Indragiri Hulu - Eko Widiyanto; Tongam Sirait (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the effect of service quality on member satisfaction at KSPPS BMT Insan Madani Indragiri Hulu. Service quality is an important factor that affects the level of satisfaction of members in using sharia cooperative services. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 151 members of KSPPS BMT Insan Madani who became research samples. The independent variable in this study is service quality, while the dependent variable is member satisfaction. Data analysis was carried out using simple linear regression to find out the extent to which service quality affects member satisfaction. The results of the study show that the quality of service has a positive and significant effect on member satisfaction. These findings show that the better the quality of service provided, the higher the level of member satisfaction will also increase. This research is expected to be an input for KSPPS BMT Insan Madani in improving the quality of its services in order to achieve optimal member satisfaction.